2016
DOI: 10.1002/cctc.201501312
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of Synergistic Catalysis of the Water‐Gas‐Shift Reaction on Cu–Au Bimetallic Surfaces

Abstract: The water‐gas‐shift reaction (WGSR) is an important industrial process that can be significantly enhanced at suitable catalyst surfaces. In this work, we investigate the catalytic behavior of metallic Cu(1 0 0) and bimetallic Cu–Au(1 0 0) surfaces. With density functional theory calculations, the variation in the Gibbs free energy (ΔG°), the activation barriers, and the rate constants for the WGSR are calculated. The variation in ΔG° for water dissociation shows that the process is spontaneous up to 520 K on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 89 publications
(219 reference statements)
0
7
0
Order By: Relevance
“…Copper, on the other hand, is reported to be more active for WGS reaction, although a significant barrier in Cu activation is required to be overcome for water dissociation [79]. Saqlain et al studied the behavior of two different catalysts, Cu 100, and bimetallic Cu-Au (100) [80]. Results indicated that the dissociation of water for the Cu (100) and bimetallic surfaces were spontaneous up to 229 K and 520 K, respectively.…”
Section: Transition Metal Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper, on the other hand, is reported to be more active for WGS reaction, although a significant barrier in Cu activation is required to be overcome for water dissociation [79]. Saqlain et al studied the behavior of two different catalysts, Cu 100, and bimetallic Cu-Au (100) [80]. Results indicated that the dissociation of water for the Cu (100) and bimetallic surfaces were spontaneous up to 229 K and 520 K, respectively.…”
Section: Transition Metal Catalystsmentioning
confidence: 99%
“…Results indicated that the dissociation of water for the Cu (100) and bimetallic surfaces were spontaneous up to 229 K and 520 K, respectively. In terms of reactivity, the study suggested that the bimetallic surface was far more reactive compared to the Cu (100) surface [80]. In another study, Wijayapala et al used catalyst systems Mo/Co/K/ ZSM-5 and Mo/Ni/K/ZSM-5 (ZSM-5 = zeolite), alone and with a copper-based WGS catalyst, for CO/H 2 ratios conversion in a batch reactor into aromatic hydrocarbons.…”
Section: Transition Metal Catalystsmentioning
confidence: 99%
“…Many of these studies involve the prediction of active catalysts based on DFT calculations that predict low energy barriers for certain reaction steps such as water dissociation, which is often cited as the rate-determining step [77,78]. Examples of catalysts that have been predicted to be active include bimetallic Au-Pd [66] and Au-Cu [79], although the applicability of these studies to supported metal catalysts is limited by their negligence of the role of the support in the reaction.…”
Section: Mechanistic and Fundamental Studiesmentioning
confidence: 99%
“…Even though these studies were not focused on catalysis, they proved the feasibility of imaging various Au-based alloys by FIM; alloys which are now used for catalysis applications: Au-Mo [228] for the reverse water-gas shift reaction [229,230] or as N 2 dissociation catalyst for the Haber-Bosch process [231], Au-Pt [224] for CO oxidation [49,232] and selective toluene oxidation [52], Au-Fe [226] for CO oxidation [233] and N 2 dissociation catalyst for the Haber-Bosch process [231], and Au-Cu [225,234] for the water gas-shift reaction [235,236] and CO oxidation [50].…”
Section: Perspectivesmentioning
confidence: 99%